1921
DOI: 10.1084/jem.33.5.593
|View full text |Cite
|
Sign up to set email alerts
|

Fate of the Lymphocyte

Abstract: Although the count of circulating lymphocytes in the blood stream remains constant, more lymphocytes enter the blood from the thoracic duct during 24 hours than are present in the blood at any one time. This excess of lymphocytes is not destroyed in the blood stream. The cells migrate from the blood vessels into the mucous membranes and through them to their surface. This occurs chiefly in the gastrointestinal tract, and it is apparently in the mucosa and especially within the intestinal lumen that the functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

1932
1932
1981
1981

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(12 citation statements)
references
References 0 publications
3
9
0
Order By: Relevance
“…Lymphoedema did not develop, but the number of lymphocytes in the peripheral blood markedly decreased, thus confirming previous reports [9,101. To what extent the resulting lymphopenia or poor recirculation of lymphocytes each individually affect the inflammatory responses to carrageenin is not easy to determine.…”
Section: The Inflammatory Response Of Rats Selectively Depleted Of Lysupporting
confidence: 91%
“…Lymphoedema did not develop, but the number of lymphocytes in the peripheral blood markedly decreased, thus confirming previous reports [9,101. To what extent the resulting lymphopenia or poor recirculation of lymphocytes each individually affect the inflammatory responses to carrageenin is not easy to determine.…”
Section: The Inflammatory Response Of Rats Selectively Depleted Of Lysupporting
confidence: 91%
“…In dogs, rabbits and cats the ligation of both right and left thoracic ducts results in a prompt fall in the peripheral blood lymphocyte number (18,19). Similar results have been obtained by diverting the lymph flow by thoracic duct cannulation (20,21,22).…”
Section: Discussionsupporting
confidence: 59%
“…The main tissues which appear to be involved in this migration are the lymph nodes, spleen, thymus, bone marrow and the gut. Although never convincingly demonstrated, many workers have suggested that some of the IE lymphocytes are normally lost into the gut lumen (4,16,18) and therefore in conditions where they are increased in number any such loss is likely to be greater. We therefore decided to study the migratory pattern of lymphocytes in normal human subjects and in those with inflammatory bowel disease and coeliac disease.…”
Section: Introductionmentioning
confidence: 99%